Observation of drastic changes in the magnetic response of epitaxial TbMnO3 thin films upon Al-doping. (April 2020) - Izquierdo, J.L.; Astudillo, A.; Martínez, J.; Bolaños, G.; Morán, O.
Abstract: The influence of Al 3+ doping on the ferromagnetic response of epitaxial TbMn1-x Alx O3 (x = 0, 0.1) thin films (~100 nm) was studied experimentally. TbMnO3 and TbMn0.9 Al0.1 O3 films (~100 nm thin) were epitaxially grown on (001)-SrTiO3 substrates by means of the high-pressure oxygen DC magnetron sputtering technique. X-ray diffraction patterns clearly showed that both films were epitaxial, with the c -axis oriented in the (00ℓ) direction. X-ray photoelectron spectroscopy analysis confirmed that the nominal valence of the Mn ions in the TbMnO3 film is 3+. Although a small shake-up peak was observed in the Mn 2p edge of the TbMn0.9 Al0.1 O3 film, depth-profiling experiments showed that the presence of this peak was only a surface effect. Anomalous ferromagnetism was observed in the pristine TbMnO3 films, which seemed to be caused by coupling between the magnetization and the epitaxial strain, due to the lattice mismatch between the film and substrate. Interestingly, drastic changes in the ferromagnetic response of the TbMnO3 films were observed upon Al 3+ substitution at the Mn 3+ positions (chemical pressure). Although Al 3+ and Mn 3+ ions are isovalent, the smaller size of the Al 3+ ions brings about further microstructural strain, which clearly influenced the ferromagnetism observed in the TbMnO3 films. The introduction of Al 3+ ions into the TbMnO3 lattice resulted in a shift of the (00ℓ) reflections to lower angles as compared with those of the TbMnO3 films. The TbMnO3 films showed a well-defined transition at ~42 K, which corresponds to the magnetic ordering temperature from the paramagnetic phase to the sinusoidal antiferromagnetic structure of the Mn spins. The antiferromagnetic transition shifted to lower temperatures for the TbMn0.9 Al0.1 O3 thin films. The experimental results demonstrated that the magnetic response of the single-phase spin-driven multiferroic TbMnO3 can effectively be tuned by both epitaxial strain and chemical pressure at the Mn site. Highlights: Epitaxial TbMnO3 and TbMn0.9 Al0.1 O3 thin films are grown via DC magnetron sputtering. Nominal valence of the Mn ions in the TbMnO3 film is 3+. Anomalous ferromagnetism is observed in pristine TbMnO3 films. Drastic changes in the ferromagnetic response of TbMnO3 films are observed upon Al 3+ substitution at the Mn 3+ positions.